Preparation of metal-semiconductor hybrid nanostructure - Gihm, Wen De (Nanyang Technological University, 2021)
Metal nanostructures have a unique property from their bulk form due to their quantum confinement effect. One of the properties that spark the interest of scientist is their optical properties in which these metal nanostructures will induce local surface plasmon resonance when they interact with light. Thus, they can be used in catalytic reactions such as water splitting and hydrogenation that involve applications to improve the quality of the environment. However, when these nanoparticles are coated with a different material, there will be an enhancement in its local surface plasmon resonance. This is mainly due to factor such as the size, shape and dielectric constant of the surrounding medium which will affect its effectiveness during its catalytic reaction. This study will mainly demonstrate the photocatalytic reaction to degrade methylene blue dye using Au as a catalyst. Au will be synthesized by seed mediated method and coated with SiO2 and Pt before exposing methylene blue dye under visible light with the catalyst. The results indicate that Au with a thinner coating of SiO2 is the most effective in degrading the methylene blue dye. Furthermore, the addition of Pt on the SiO2 would enhance the rate of degradation further. However, factors like agglomeration can also affect the effectiveness of the degradation.